The Use of vegetation to reduce Landslide hazards in Malaysia - Lateh, Habibah; Avani, Nazi (International Journal of Engineering and Technology, 2018)
The use of vegetation as slope cover becomes an alternative solution for slope stabilization instead of using structural or hard method of engineering techniques. Use of vegetation is a way to reduce the impact of engineering works and increase the landscape quality. Engineers usually are not familiar with engineering properties of vegetation to reduce slope instability and shallow landslide. Therefore, in this research, the soil engineering properties of two tropical species were studied. Eight trees of similar age of Acacia mangium and Macaranga tanarius were selected along the East-West highway, Malaysia. The direct shear tests were used to analyze the effect of tree roots on soil mechanical properties (soil cohesion and internal friction angle). The results showed that the existence of roots has more impact on the soil cohesion than the soil internal friction angle. In conclusion, slope stability improvement is provided by increasing the additional soil cohesion due to root.